2010
DOI: 10.1093/nar/gkq053
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants of specific DNA-recognition by the THAP zinc finger

Abstract: Human THAP1 is the prototype of a large family of cellular factors sharing an original THAP zinc-finger motif responsible for DNA binding. Human THAP1 regulates endothelial cell proliferation and G1/S cell-cycle progression, through modulation of pRb/E2F cell-cycle target genes including rrm1. Recently, mutations in THAP1 have been found to cause DYT6 primary torsion dystonia, a human neurological disease. We report here the first 3D structure of the complex formed by the DNA-binding domain of THAP1 and its sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
87
0
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 47 publications
6
87
0
1
Order By: Relevance
“…This mutual interdependence of HCF-1 and a sequence-specific transcription factor has not been described previously and may represent a unique feature of THAP11. Recent structural analyses of prototypical THAP domains bound to their respective DNA elements have revealed that THAP proteins bind DNA in a bipartite manner, making simultaneous major-and minor-groove DNA contacts (5,35). Nonspecific contacts with the sugar-phosphate backbone of the minor groove are critical for THAP domain binding to DNA and are mediated primarily by basic amino acids present in a flexible loop structure positioned between the zinc-coordinating residues and the conserved AVPTIF box.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This mutual interdependence of HCF-1 and a sequence-specific transcription factor has not been described previously and may represent a unique feature of THAP11. Recent structural analyses of prototypical THAP domains bound to their respective DNA elements have revealed that THAP proteins bind DNA in a bipartite manner, making simultaneous major-and minor-groove DNA contacts (5,35). Nonspecific contacts with the sugar-phosphate backbone of the minor groove are critical for THAP domain binding to DNA and are mediated primarily by basic amino acids present in a flexible loop structure positioned between the zinc-coordinating residues and the conserved AVPTIF box.…”
Section: Discussionmentioning
confidence: 99%
“…THAP domains are approximately 80 to 90 amino acids in length and, in addition to zinc-coordinating residues, contain several conserved or invariant residues necessary for proper domain folding and DNA-binding activity (4,5,7,35). The majority of conserved THAP proteins also contain a coiled-coil protein interaction domain adjacent to a host cell factor 1 (HCF-1)-binding motif (HBM) (26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is supported by three additional notions: first, the amino acids isoleucine and valine have a similar structure and both belong to the unpolar amino acids. Second, Campagne et al 21 revealed lysine 70 as the most C-terminal amino acid residue responsible for DNA binding by detailed structural determination of the THAP domain. Thus, isoleucine 80 should not be involved in DNA binding.…”
Section: Discussionmentioning
confidence: 99%
“…Pretpostavlja se da bi THAP proteini preko coiledcoil domena mogli da posreduju u proteinskim interakcijama. Pokazano je da monomer THAP1 proteina ima nizak afinitet vezivanja za DNK (Campagne at al., 2010) i da in vivo THAP1 verovatno funkcioniše kao homodimer u okviru nekog većeg multimernog DNKvezujućeg kompleksa (Sengel et al, 2011). Slika 4.…”
Section: Molekularno Genetička Osnova Dyt6unclassified